Active Viewing: A Strategy to Boost Listening and Speaking Skill in English Learners - Rizki Dian Retno; Edi Trisno (Universitas Pendidikan Ganesha, 2024)
Listening and speaking are two essential skills students must master in the classroom. However, many students still need help improving their listening and speaking skills in English. Therefore, this study aims to explore the effectiveness of active viewing. This research is experimental. This research used a pre-test-post-test design for experimental and control groups. Determination of the sample using a purposive sampling technique. The research sample was 22 class XII BDP 2 students as the experimental group and 19 class XII BDP 1 students as the control. The methods used to collect data are observation and tests. The instruments used to collect data were test questions and observation lists. The technique used to analyze data is inferential statistics. The research results show that the average score from the post-test in the experimental class is 66.36, and the average score from the post-test in the control class is 47.89 in terms of listening skills. In addition, the average score from the post-test in the experimental class was 74.55, and the average score in the control class was 57.89 in terms of speaking skills. The results showed that the average post-test score in the experimental class was higher than the average post-test score in the control class. Based on these results, it is concluded that active viewing techniques are more effective than conventional techniques, especially for improving students' listening and speaking skill.